Dear black girl : letters fom your sisters on stepping into your power - Winfrey Harris, Tamara (Berrett-Koehler Publishers, 2021)
"Dear Black Girl is the empowering, affirming love letter our girls need in order to thrive in a world that does not always protect, nurture, or celebrate us. This collection of Black women's voices ... is a must-read, not only for Black girls, but for everyone who cares about Black girls, and for Black women whose inner-Black girl could use some healing."--Tarana Burke, Founder of the 'Me Too' Movement"Dear Dope Black Girl, You don't know me, but I know you. I know you because I am you! We are magic, light, and stars in the universe." So begins a letter that Tamara Winfrey Harris received as part of her Letters to Black Girls project, where she asked black women to write honest, open, and inspiring letters of support to young black girls aged thirteen to twenty-one. Her call went viral, resulting in a hundred personal letters from black women around the globe that cover topics such as identity, self-love, parents, violence, grief, mental health, sex, and sexuality. In Dear Black Girl, Winfrey Harris organizes a selection of these letters, providing "a balm for the wounds of anti-black-girlness" and modeling how black women can nurture future generations. Each chapter ends with a prompt encouraging girls to write a letter to themselves, teaching the art of self-love and self-nurturing. Winfrey Harris's The Sisters Are Alright explores how black women must often fight and stumble their way into alrightness after adulthood. Dear Black Girl continues this work by delivering pro-black, feminist, LGBTQ+ positive, and body positive messages for black women-to-be--and for the girl who still lives inside every black woman who still needs reminding sometimes that she is alright